Active and authentic learning in DietitianJr@UKMTM : preparing dietetic students for the future jobs - Nur Hana Hamzaid,; Nor Aini Jamil,; Nurul Huda Razalli,; Nik Shanita Safii, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Dietetic profession has grown from mainly clinical setting to several other settings that was not thought possible until recently such as hosting healthy cooking shows to personalised online consultation. With the similar number of credit hours allocated for first degree dietetics students, conventional method of teaching would not be sufficient in preparing them for endless opportunity of working world. Hence, active learning is a timely approach in addressing this issue. The objective of this paper is to introduce a newly created program (DietitianJr@UKMTM) that applied active learning in equipping dietetics first degree students with skills that may be useful for the unconventional future jobs. DietitianJr@UKMTM is an annual program created in fulfilling Patient Education course outcome that involves community. Dietetics students were divided into four groups that introduced them to four main working areas of a Dietitian, i.e. inpatient, outpatient, food service and community service. Several stages were involved starting with lectures and case study discussions on basic concept and protocol of creating patient education material, followed by a need’s assessment survey, creating educational tools and a minimum of four discussion sessions with supervisors. This program was conducted among primary school children (aged 8-11 years) with the objective of introducing healthy eating concept and dietitian career. Results shows a highly positive feedback from the participants for each of the three-year school-holiday program. It is hoped that this fun-learning program will not only provide experience to dietetic students through authentic learning, but also educating the community on healthy eating and the importance role of dietitians.